The problem of evil in Arendt's work Analysis of the legal dimension (2021)
Radical evil and the banality of evil are the two ways in which Arendt has cataloged totalitarian evil at different stages of his work. The aim of this paper is to approach the different Arendtian conceptions of evil from a legal perspective in order to determine whether there are continuities or whether, on the contrary, there is an abrupt change in Arendt’s thinking. The difficulty that must be faced is that the problem of evil and the legal question are not issues addressed by Arendt directly but are transversal contents that must be traced in the totality of his work. It is concluded that radical evil and the banality of evil are not mutually exclusive notions but rather function as expressions that refer to two different levels, one more general and structural and the other linked to the behavior of individuals within the government structures studied.